The clinical efficacy and influencing factors of uterine artery embolization in the treatment of different types of uterine adenomyosis - Wen-Jiang Wei; Zuo-Fu Tian; Hao Liu; Cheng-Jiang Xiao (Scientific Reports)
Abstract Uterine adenomyosis, a common benign tumor disease in gynecology, mainly manifested as chronic pelvic pain, menstrual disorders, dysmenorrhea, etc., has a great impact on patients’ daily life and work. Compared with traditional surgery and drug therapy, uterine artery embolization (UAE), as a new treatment with less trauma, faster recovery and uterine preservation, can relieve pain while preserving normal physiological and reproductive functions of the uterus, which is favored by the majority of patients. In this study, the patients were divided into two groups based on magnetic resonance imaging (MRI) test. Their serum CA125 level was detected, and the degree of symptom relief and health index were evaluated, aiming to explore the clinical efficacy and influencing factors of UAE in the treatment of adenomyosis. The results showed that before UAE, CA125 level in group B was significantly higher than that in group A, and 2 days after UAE, CA125 level in both groups was lower than before treatment, indicating that the serum CA125 level may be related to the type of adenomyosis, but UAE has a good therapeutic effect on both focal and diffuse adenomyosis. 3 months after interventional treatment, the patients had significantly reduced symptoms with dramatically improved health status and the VAS pain score was significantly reduced, indicating that UAE can significantly improve the clinical symptoms of patients with adenomyosis. Uterine artery embolization was performed in both groups. No serious complications occurred during the operation, and the technical success rate reached 100%. In summary, UAE, as a minimally invasive treatment, has obvious and significant clinical effects in the treatment of adenomyosis, and is an important alternative treatment for adenomyosis.